Cyano polymer material with rigid framework as well as preparation method and application of cyano polymer material

By modifying PEI to prepare cyano polymers and hydrogel fabrics, the shortcomings of alumina and PEI in the preparation of LSA99Mo/99mTc generators in the prior art have been overcome, and efficient adsorption and selective separation of molybdenum metal ions have been achieved.

CN121005899APending Publication Date: 2025-11-25SHANGHAI HUAHE PHARM CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511160371.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-19
Publication Date
2025-11-25

AI Technical Summary

Technical Problem

In the existing technology, ordinary alumina is not suitable for preparing low specific activity 99Mo/99mTc generators, and polyethyleneimine (PEI) has a limited range of applications in solid-liquid adsorption separation. There is an urgent need for modified compounds to improve the utilization rate of LSA99Mo.

Method used

By preparing cyano polymers with rigid skeletons and modifying functional polymers such as PEI, cyano polymers and hydrogel fabrics are formed for adsorption and separation of isotope 99Mo metal ions.

Benefits of technology

It achieves high adsorption capacity for molybdenum metal ions, significantly improves the utilization rate of LSA99Mo, and exhibits excellent stability and selectivity in molybdenum-technetium separation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121005899A_ABST
    Figure CN121005899A_ABST
Patent Text Reader

Abstract

The invention relates to a cyano polymer material with a rigid framework as well as a preparation method and application of the cyano polymer material. Specifically, the invention provides a cyano polymer with a rigid skeleton as shown in a formula I, and polyethyleneimine (PEI) is grafted on the cyano polymer for modification by using an irradiation crosslinking technology to form a hydrogel adsorption material, so that the hydrogel adsorption material has excellent mechanical strength, moldability and adsorption separation function. The hydrogel material has a good result in the field of molybdenum and technetium separation, provides a new idea for separating < 99m > Tc from < 99Mo, and has a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of polymer adsorption and separation materials technology, specifically relating to a cyano polymer material with a rigid framework, its preparation method, and its application. Background Technology

[0002] Currently, the use of enrichment targets based on reactors / accelerators ( 98 / 100 Mo) Production of medical isotopes 99 Mo's methods have been extensively explored, for example 98 Mo(n, γ) 99 Mohe 100 Mo(γ, n) 99 Mo, etc. Currently, 75 operating research reactors are capable of... 98 Mo(n,γ) 99 Made in Mo 99 Mo. Canada has been working to produce through accelerators. 99 Mo, with 100 Mo(γ,n) 99 Backed by Mo, the program received support from the Canadian government (the Non-Reactor Isotope Supply Program (2010) and the Isotope Technology Acceleration Program (2012)). These were all obtained through [unclear - likely referring to funding or funding]. 99 Mo's simple approach can eliminate the generation of radioactive waste, reducing the risk and cost of nuclear proliferation. Typically, this is achieved through... 98 Mo(n,γ) 99 Mohe 100 Mo(γ,n) 99 The low specific activity (LSA) produced by Mo 99 Mo (e.g., approximately 0.35-15 Cig) -1 A column absorbent with high molybdenum ion absorption capacity is needed to prepare the 99Mo / 99mTc generator. Unfortunately, this is not suitable for fission. 99 Mo / 99m The ordinary alumina (containing 2-20 mg of molybdenum per gram of alumina) used in Tc generators is not suitable for preparing LSA. 99 Mo / 99 mTc generator. Therefore, there is an urgent need for... 99 Separation from Mo 99m The Tc method was studied to improve LSA 99 Mo usage rate.

[0003] Polyethyleneimine (PEI), as a functional polymer, possesses excellent hydrophilicity and thermal stability. Containing a large number of amino groups (primary and secondary amines), it exhibits strong cationic polymer properties in water, demonstrating strong chelating and ion exchange capabilities, making it suitable as an adsorbent material. However, due to PEI's high water solubility, its application in solid-liquid adsorption and separation is limited.

[0004] Therefore, there is an urgent need in this field for a novel compound to modify functional polymers such as PEI, which can adsorb metal ions during solid-liquid separation to overcome the shortcomings of existing technologies. Summary of the Invention

[0005] The purpose of this invention is to provide a cyano polymer with a rigid backbone for modifying functional polymers such as PEI, thereby achieving the modification of isotopes. 99 Adsorption and separation of Mo metal ions.

[0006] In a first aspect, the present invention provides a cyano polymer having the structure shown in Formula I.

[0007]

[0008] Where n is any integer from 80 to 95.

[0009] In another preferred embodiment, the method for preparing the cyano polymer includes the following steps:

[0010]

[0011] (a1) 2,6-Difluorobenzonitrile and p-nitrophenol were heated and reacted to obtain compound Ia in the presence of inert solvent 1 and catalyst 1.

[0012] (b1) In the presence of inert solvent 2 and catalyst 2, compound Ia reacts with reducing agent R, and after filtration, standing and drying, compound Ib is obtained;

[0013] (c1) In the presence of inert solvent 3 and catalyst 3, compound Ib is polymerized with 4,4'-oxobisphthalic anhydride at high temperature to obtain a white fibrous solid, which is compound I.

[0014] Where n is as described above.

[0015] In another preferred embodiment, the molar ratio of 2,6-difluorobenzonitrile to p-nitrophenol in step (a1) is 1:1.

[0016] In another preferred embodiment, the reaction time of step (a1) is 4 to 8 hours.

[0017] In another preferred embodiment, the inert solvent 1 is selected from the group consisting of N,N-dimethylformamide, N,N-dimethylacetamide, N,N-diethylformamide, N-methylpyrrolidone, or combinations thereof.

[0018] In another preferred embodiment, the amount of inert solvent 1 added is 2 to 5 times the mass of 2,6-difluorobenzonitrile.

[0019] In another preferred embodiment, the catalyst 1 is selected from the group consisting of potassium carbonate, sodium carbonate, potassium hydroxide, and sodium hydroxide.

[0020] In another preferred embodiment, the amount of catalyst 1 added is 1 to 5 times the mass of 2,6-difluorobenzonitrile.

[0021] In another preferred embodiment, the heating reaction in step (a1) is a gradient heating, comprising a first gradient and a second gradient.

[0022] In another preferred embodiment, the temperature of the first gradient is 80–100°C.

[0023] In another preferred embodiment, the temperature of the second gradient is 100–140°C.

[0024] In another preferred embodiment, the gradient heating is intended to accelerate dissolution.

[0025] In another preferred embodiment, step (a1) further includes sedimentation, drying and purification processes after the heating reaction is complete.

[0026] In another preferred embodiment, the reaction time of step (b1) is 5 to 7 hours.

[0027] In another preferred embodiment, the reaction temperature of step (b1) is 90–100°C.

[0028] In another preferred embodiment, the inert solvent 2 is selected from the group consisting of ethanol, methanol, water, toluene, ethylene glycol dimethyl ether, or combinations thereof.

[0029] In another preferred embodiment, the amount of inert solvent 2 added is 5 to 10 times the mass of compound Ia.

[0030] In another preferred embodiment, the catalyst 2 is selected from the group consisting of Pd / C, Ni(R), or combinations thereof.

[0031] In another preferred embodiment, the amount of catalyst 2 added is 0.1 to 0.3 times the mass of compound Ia.

[0032] In another preferred embodiment, the reducing agent R is selected from the group consisting of hydrazine hydrate, iron powder, or combinations thereof.

[0033] In another preferred embodiment, the amount of reducing agent R added is 0.1-0.5 times the mass of compound Ia.

[0034] In another preferred embodiment, the molar ratio of compound Ib to 4,4'-oxophthalic anhydride in step (c1) is 1:1.

[0035] In another preferred embodiment, the high-temperature reaction in step (c1) is 170–200°C.

[0036] In another preferred embodiment, the reaction time of step (c1) is 3 to 4 hours.

[0037] In another preferred embodiment, the inert solvent 3 is selected from the group consisting of m-cresol, o-dichlorobenzene, p-chlorophenol, or combinations thereof.

[0038] In another preferred embodiment, the amount of inert solvent 3 added is 5 to 10 times the mass of compound Ib.

[0039] In another preferred embodiment, the catalyst 3 is selected from the group consisting of isoquinoline, benzoic acid, or combinations thereof.

[0040] In another preferred embodiment, the mass concentration of the catalyst 3 in the inert solvent 3 is 1-4%.

[0041] In a second aspect, the present invention provides a hydrogel fabric, the preparation method of which is as follows:

[0042] (1) In the presence of inert solvent 4 and catalyst 4, the compound of formula I as described in the first aspect of the present invention is mixed with amino-modified reaction precursor N and heated to form a first solution;

[0043] (2) Add crosslinking agent C to the first solution and stir thoroughly to form a second solution;

[0044] (3) Mix the second solution with the fabric so that the fabric is completely soaked in the second solution;

[0045] (4) The fabric obtained in step (3) is subjected to irradiation crosslinking to obtain hydrogel fabric.

[0046] In another preferred embodiment, the inert solvent 4 is selected from the group consisting of ethanol, methanol, water, or combinations thereof; and / or

[0047] The catalyst 4 is selected from the group consisting of sodium hydroxide, sodium bicarbonate, potassium hydroxide, lithium hydroxide, or combinations thereof.

[0048] In another preferred embodiment, the amount of the inert solvent 4 added is 2 to 5 times that of the compound of formula I.

[0049] In another preferred embodiment, the concentration of catalyst 4 is 0.1–0.5 mol / L.

[0050] In another preferred embodiment, the catalyst 4 is added in an amount of 0.01 to 0.05 mol.

[0051] In another preferred embodiment, the mass ratio of the compound of formula I to the amino-modified reaction precursor N is 1:5 to 10.

[0052] In another preferred embodiment, the amino-modified reaction precursor N is selected from the group consisting of: Hyperbranched polypropyleneimide;

[0053] Where m ranges from 3000 to 70000.

[0054] In another preferred embodiment, the amino-modified reaction precursor N is

[0055] In another preferred embodiment, step (1) is the following reaction:

[0056]

[0057] In another preferred embodiment, the crosslinking agent C is selected from the group consisting of: N,N'-methylenebisacrylamide (MBA), triethanolamine, titanate crosslinking agent (TA), epichlorohydrin, and glutaraldehyde.

[0058] In another preferred embodiment, the ratio of the crosslinking agent C to the first solution is 1 wt% to 2 wt%.

[0059] In another preferred embodiment, the fabric is selected from the group consisting of: nonwoven fabric and cotton fabric.

[0060] In another preferred embodiment, the irradiation source is an electron accelerator and a cobalt source.

[0061] In another preferred embodiment, the irradiated absorbed dose ranges from 10 to 100 kGy.

[0062] In another preferred embodiment, the irradiation absorbed dose rate is 1 kGy / s.

[0063] In another preferred embodiment, the irradiation temperature is 20–35°C.

[0064] In another preferred embodiment, the irradiation atmosphere is nitrogen.

[0065] A third aspect of the present invention provides the use of a cyanopolymer as described in the first aspect of the present invention or a hydrogel fabric as described in the second aspect of the present invention.

[0066] i) Used for the adsorption and separation of metal ions;

[0067] ii) Used to prepare isotopes 99 Mo reactor.

[0068] In another preferred embodiment, the metal ion is selected from the group consisting of molybdenum (Mo), technetium (Tc), rhenium (Re), or combinations thereof.

[0069] It should be understood that, within the scope of this invention, the above-described technical features of this invention and the technical features specifically described below (such as in the embodiments) can be combined with each other to form new or preferred technical solutions. Due to space limitations, they will not be described in detail here. Attached Figure Description

[0070] Figure 1 The compound I-a obtained in Example 1 is shown. Figure 1 a) Compound II-b Figure 1 b) The hydrogen NMR spectrum.

[0071] Figure 2 The 1H NMR spectrum of the cyanopolymer of Formula I obtained in Example 1 is shown.

[0072] Figure 3 The breakthrough curve of the polymer CNPI nonwoven composite material in a mixed solution of Mo and Re is shown.

[0073] Figure 4 The polymer CNPI nonwoven composite material was shown in 99 Different volumes of eluent in Mo solution 99 elution rate of mTc and 99 Cumulative elution rate of mTc. Detailed Implementation

[0074] Through extensive and in-depth research, the inventors unexpectedly developed a cyano polymer (compound of formula I) with a rigid backbone, which exhibits excellent stability. When this cyano polymer is prepared into a hydrogel fabric, it demonstrates a high adsorption capacity for molybdenum (Mo) metal ions, thereby achieving the separation of molybdenum and technetium. Based on this, the present invention was completed.

[0075] the term

[0076] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art to which this invention pertains.

[0077] As used herein, the terms “comprising,” “including,” and “containing” are used interchangeably and include not only closed definitions but also semi-closed and open definitions. In other words, the terms include “consisting of” and “substantially consisting of”.

[0078] Compound of Formula I and its preparation method are hereby invented.

[0079] This invention provides a cyano polymer with the structure shown in Formula I.

[0080]

[0081] Where n is any integer from 80 to 95.

[0082] In this invention, the preparation method of the compound of formula I is as follows:

[0083]

[0084] (a1) 2,6-Difluorobenzonitrile and p-nitrophenol were heated and reacted to obtain compound Ia in the presence of inert solvent 1 and catalyst 1.

[0085] (b1) In the presence of inert solvent 2 and catalyst 2, compound Ia reacts with reducing agent R, and after filtration, standing and drying, compound Ib is obtained;

[0086] (c1) In the presence of inert solvent 3 and catalyst 3, compound Ib is polymerized with 4,4'-oxobisphthalic anhydride at high temperature to obtain a white fibrous solid, which is compound I.

[0087] Where n is as described above.

[0088] Hydrogel fabrics and their preparation methods

[0089] This invention provides a hydrogel fabric, the preparation method of which is as follows:

[0090] (1) In the presence of inert solvent 4 and catalyst 4, the compound of formula I as described above is mixed with amino-modified reaction precursor N and heated to form a first solution;

[0091]

[0092] (2) Add crosslinking agent C to the first solution and stir thoroughly to form a second solution;

[0093] (3) Mix the second solution with the fabric so that the fabric is completely soaked in the second solution;

[0094] (4) The fabric obtained in step (3) is subjected to irradiation crosslinking to obtain hydrogel fabric.

[0095] in,

[0096] The amino-modified reaction precursor N is selected from the following group: Hyperbranched polypropyleneimide;

[0097] Where m ranges from 3000 to 70000.

[0098] The crosslinking agent C is selected from the following group: N,N'-methylenebisacrylamide (MBA), triethanolamine, titanate crosslinking agent (TA), epichlorohydrin, and glutaraldehyde.

[0099] The fabric is selected from the group consisting of: non-woven fabric and cotton fabric.

[0100] Compared with the prior art, the main advantages of the present invention are:

[0101] (1) The cyano polymer with a rigid skeleton (compound of formula I) described in this invention has excellent thermal stability, chemical resistance, radiation resistance, mechanical strength and flexibility.

[0102] (2) The compound of Formula I described in this invention has a high glass transition temperature, which can better adapt to the processing of materials and has good application prospects.

[0103] (3) The hydrogel fabric described in this invention has significant effects in the field of molybdenum and technetium adsorption and separation. It has a high adsorption capacity for molybdenum and a very weak adsorption capacity for technetium, thereby achieving the separation of molybdenum and technetium.

[0104] The present invention will be further illustrated below with reference to specific embodiments. It should be understood that these embodiments are for illustrative purposes only and are not intended to limit the scope of the invention. Experimental methods in the following embodiments, unless otherwise specified, are generally performed under conventional conditions or as recommended by the manufacturer. Unless otherwise stated, percentages and parts are weight percentages and parts by weight.

[0105] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as are familiar to those skilled in the art. Furthermore, any methods and materials similar to or equivalent to those described herein may be applied to the methods of this invention. The preferred embodiments and materials described herein are for illustrative purposes only.

[0106] In this invention, the structure of the compound was determined by nuclear magnetic resonance (NMR). The NMR measurements were performed using a Bruker AVANCE-400 NMR spectrometer.

[0107] Example 1: Preparation of Compound I

[0108] (1) The synthetic steps of 2,6-bis(4-nitrophenoxy)benzonitrile (compound I-a) are as follows:

[0109] Under a nitrogen atmosphere, 13.91 g (100 mmol) of 2,6-difluorobenzonitrile and 27.82 g (100 mmol) of p-nitrophenol were added to 100 mL of stirred solution of N,N-dimethylformamide (DMF), followed by the addition of 80 mL of potassium carbonate (K₂CO₃) solution (27.64 g (100 mmol)). The mixture was heated to 100 °C to accelerate dissolution. The temperature was then raised to 140 °C to initiate the reaction. After 6 h, when the solution color changed from yellow to dark green, the reactants were poured into an aqueous methanol solution for precipitation. The reactants were filtered and dried at 60 °C for 6 h. The crude solid was purified by silica gel column chromatography and eluted with dichloromethane to obtain a light yellow solid. The 1H NMR spectrum of the obtained compound I-a is shown below. Figure 1 As shown.

[0110] (2) The preparation steps of 2,6-bis(4-aminophenoxy)benzonitrile (compound Ib) are as follows:

[0111] 2,6-bis(4-nitrophenoxy)benzonitrile (15.09 g, 40 mmol) and palladium on carbon catalyst (Pd / C, 5%) were heated to 95 °C in 200 mL of stirred ethanol. Then, 15 mL of 50% hydrazine hydrate was gradually added dropwise to the reactants over 1 h. When the reactants became a clear black solution, they were filtered while hot. The filtrate was allowed to stand for a period of time, during which a pale yellow solid precipitated. This filtrate was filtered and dried at 60 °C for 12 h to obtain a pale white solid, I. The 1H NMR spectrum of the obtained compound Ib is shown below. Figure 1 As shown;

[0112] (3) The preparation method of the cyano polymer (compound of formula I) is as follows:

[0113] Under a nitrogen atmosphere, 2,6-bis(4-aminophenoxy)benzonitrile (1.5868 g, 5 mmol) and 4,4'-oxophthalic anhydride (ODPA) (1.5511 g, 5 mmol) were heated to 195 °C in 12 mL of stirred m-cresol solution. Then, a small amount (approximately 9-12 drops) of isoquinoline was added as a catalyst, and the mixture was heated under reflux for 3-4 h. After the reaction was complete, the viscous reactant was poured into a stirred ethanol solution to form fibrous material. The material was then repeatedly soaked in alternating ethanol and hot water solutions, dried at 60 °C for 12 h, and then dried in a vacuum oven at 200 °C for 1 h to remove the solvent, yielding a creamy white fibrous solid. The 1H NMR spectrum of the obtained cyanopolymer is shown below. Figure 2 As shown.

[0114] Example 2

[0115] In this embodiment, a method for forming a hydrogel by irradiation crosslinking of a rigid-frame cyano polymer PEI includes the following steps:

[0116] (1) The cyano compound (0.3g) and PEI (3g) were heated to 60°C in 25ml of sodium hydroxide methanol water stirring solution and reacted for 12h. The whole solution was a clear and transparent yellow solution.

[0117] (2) Add 2% (by mass) of crosslinking agent MBA to the entire solution and stir thoroughly to dissolve it in the solution;

[0118] (3) Pour the completely dissolved solution into a glass dish, add the fabric to the glass dish, and let the solution completely soak the fabric.

[0119] (4) It is placed in a cobalt source irradiation field for irradiation. The irradiation absorbed dose is 50 kGy, the dose rate is 1 kGy / s, the irradiation temperature is room temperature, and the irradiation atmosphere is air. The irradiation crosslinking is carried out to form a hydrogel fabric.

[0120] Example 3

[0121] In this embodiment, a method for forming a hydrogel by irradiation crosslinking of a rigid-frame cyano polymer PEI includes the following steps:

[0122] (1) The cyano compound (0.15g) and PEI (1.5g) were heated to 60°C in 12.5ml sodium hydroxide methanol water stirring solution and reacted for 12h. The whole solution was a clear and transparent yellow solution.

[0123] (2) Add 1% (by mass) of crosslinking agent MBA to the entire solution and stir thoroughly to dissolve it in the solution;

[0124] (3) Pour the completely dissolved solution into a glass dish, add the fabric to the glass dish, and let the solution completely soak the fabric.

[0125] (4) It is placed in an electron beam irradiation field for irradiation. The irradiation absorbed dose is 10 kGy, the dose rate is 1 kGy / s, the irradiation temperature is room temperature, and the irradiation atmosphere is nitrogen. The irradiation crosslinks are then carried out to form a hydrogel fabric.

[0126] Example 4

[0127] In this embodiment, a method for forming a hydrogel by irradiation crosslinking of a rigid backbone cyanopolymer PEI includes the following steps:

[0128] (1) The cyano compound (0.3g) and PEI (3g) were heated to 60°C in 25ml of sodium hydroxide methanol water stirring solution and reacted for 12h. The whole solution was a clear and transparent yellow solution.

[0129] (2) Add 2% (by mass) of crosslinking agent MBA to the entire solution and stir thoroughly to dissolve it in the solution;

[0130] (3) Pour the completely dissolved solution into a glass dish, add the fabric to the glass dish, and let the solution completely soak the fabric.

[0131] (4) It is placed in a cobalt source irradiation field for irradiation. The irradiation absorbed dose is 30 kGy, the dose rate is 1 kGy / s, the irradiation temperature is room temperature, and the irradiation atmosphere is nitrogen. The irradiation crosslinking is carried out to form a hydrogel fabric.

[0132] Example 5

[0133] In this embodiment, a method for forming a hydrogel by irradiation crosslinking of a rigid backbone cyanopolymer PEI includes the following steps:

[0134] (1) The cyano compound (0.6g) and PEI (6g) were heated to 60°C in 50ml of sodium hydroxide methanol water stirring solution and reacted for 12h. The whole solution was a clear and transparent yellow solution.

[0135] (2) Add 2% (by mass) of crosslinking agent MBA to the entire solution and stir thoroughly to dissolve it in the solution;

[0136] (3) Pour the completely dissolved solution into a glass dish, add the fabric to the glass dish, and let the solution completely soak the fabric.

[0137] (4) It is placed in a cobalt source irradiation field for irradiation. The irradiation absorbed dose is 70 kGy, the dose rate is 1 kGy / s, the irradiation temperature is room temperature, and the irradiation atmosphere is nitrogen. The irradiation crosslinks are then carried out to form a hydrogel fabric.

[0138] Example 6

[0139] In this embodiment, a method for forming a hydrogel by irradiation crosslinking of a rigid-frame cyano polymer PEI includes the following steps:

[0140] (1) The cyano compound (0.6g) and PEI (6g) were heated to 60°C in 50ml of sodium hydroxide methanol water stirring solution and reacted for 12h. The whole solution was a clear and transparent yellow solution.

[0141] (2) Add 1.5% (by mass) of crosslinking agent MBA to the whole solution and stir thoroughly to dissolve it in the solution;

[0142] (3) Pour the completely dissolved solution into a glass dish, add the fabric to the glass dish, and let the solution completely soak the fabric.

[0143] (4) It is placed in an electron beam irradiation field for irradiation. The irradiation absorbed dose is 100 kGy, the dose rate is 1 kGy / s, the irradiation temperature is room temperature, and the irradiation atmosphere is air. The irradiation crosslinks are then carried out to form a hydrogel fabric.

[0144] Example 7

[0145] In this embodiment, the application of a rigid skeleton cyano polymer PEI modified by radiation crosslinking to form a hydrogel material is described. The experimental method is as follows:

[0146] 1. Among the grafted polymer materials mentioned above, those with amine chelating functional groups can be used for the adsorption and separation of molybdenum and technetium metal ions;

[0147] 2. The hydrogel fabrics of each embodiment were placed in a solution containing molybdenum and technetium metal ions for adsorption and separation. The adsorption capacity was calculated by the difference in the concentration of each ion in the solution and the mass of the material added, as shown in Table 1 below (the chemical properties of Tc are very similar to those of Re, so Re ions can be used to replace Tc ions in all absorption studies to study the absorption properties).

[0148] Table 1

[0149]

[0150] Experimental results: It can be seen that with increasing irradiation absorption dose, the adsorption capacity of the hydrogel material for Mo decreases, while the adsorption capacity for Re changes less. This indicates that the irradiation absorption dose has an impact on the adsorption capacity of the hydrogel, but this effect is within a controllable range.

[0151] Example 8

[0152] In this embodiment, an application of a rigid skeleton cyanopolymer PEI modified by irradiation crosslinking to form a hydrogel material is described.

[0153] Experimental Method: The gel fabric from Example 2 was cut into 7 mm diameter sheets and packed into an adsorption column of the same diameter, with a packing mass of 0.05 g. A molybdenum-containing solution (pH 3, initial concentration 2500 ppm, flow rate 1.0 ml / min) was pumped into the column. Each 2 ml eluent was collected. The concentration of Mo in the initial solution and eluent was determined using inductively coupled plasma optical emission spectrometry (ICP-OES).

[0154] Experimental results: such as Figure 3 The breakthrough curves of the mixed Mo-Re (2500 mg / L) are shown. When Ct / C0 is approximately 0.05, the breakthrough point of Mo occurs at a bed volume (BV) of 24, while Re penetrates the column almost immediately. This significant selectivity confirms that the material has a stronger affinity for Mo than Re and highlights its superior separation performance in the generator system. 99m Tc and 99 The promising future of Mo.

[0155] Example 9

[0156] In this embodiment, the purpose is to realize the practical application of irradiation crosslinking of rigid skeleton cyanopolymer PEI to form hydrogel materials.

[0157] Experimental Method: Approximately 0.5 g of the gel fabric from Example 2 was cut into slices and packed into an adsorption column (7 mm × 10 mm). The column was pretreated with 50 ml of nitric acid solution at pH 3. Subsequently, under conditions of pH 3 and a flow rate of 1.0 ml / min, the gel fabric was... 99 A Mo (7.29 mCi) solution was loaded onto the column. The column was then washed with 20 mL of nitric acid solution (pH 3), followed by 100 mL of physiological saline. Eluent was then collected every 2 min with physiological saline at a flow rate of 1.0 mL / min. The eluent was measured using a radioactivity meter. 99 Mohe 99m The radioactivity of Tc. The purity of the radionuclide was determined using a gamma-ray detector.

[0158] Experimental results: Figure 4 for 99m Elution and accumulation curves of Tc were obtained. Approximately 90% of the Tc was collected in 25 ml of physiological saline. 99m Tc.

[0159] All documents mentioned in this invention are incorporated herein by reference as if each document were individually incorporated by reference. Furthermore, it should be understood that after reading the foregoing teachings of this invention, those skilled in the art can make various alterations or modifications to this invention, and these equivalent forms also fall within the scope defined by the appended claims.

Claims

1. A cyanopolymer having the structure shown in Formula I, 2. The cyano polymer as described in claim 1, characterized in that, Its preparation method includes the following steps: (a1) 2,6-Difluorobenzonitrile and p-nitrophenol were heated and reacted to obtain compound Ia in the presence of inert solvent 1 and catalyst 1. (b1) In the presence of inert solvent 2 and catalyst 2, compound Ia reacts with reducing agent R, and after filtration, standing and drying, compound Ib is obtained; (c1) In the presence of inert solvent 3 and catalyst 3, compound Ib is polymerized with 4,4'-oxobisphthalic anhydride at high temperature to obtain a white fibrous solid, which is compound I. Wherein, n is as described in claim 1.

3. The cyano polymer as described in claim 2, characterized in that, In step (c1), the molar ratio of compound Ib to 4,4'-oxophthalic anhydride is 1:

1.

4. The cyano polymer as described in claim 2, characterized in that, The inert solvent 3 is selected from the group consisting of m-cresol, o-dichlorobenzene, p-chlorophenol, or combinations thereof.

5. The cyano polymer as described in claim 2, characterized in that, The catalyst 3 is selected from the group consisting of isoquinoline, benzoic acid, or combinations thereof.

6. A hydrogel fabric, characterized in that, Its preparation method is as follows: (1) In the presence of inert solvent 4 and catalyst 4, the compound of formula I as described in claim 1 is mixed with amino-modified reaction precursor N and heated to form a first solution; (2) Add crosslinking agent C to the first solution and stir thoroughly to form a second solution; (3) Mix the second solution with the fabric so that the fabric is completely soaked in the second solution; (4) The fabric obtained in step (3) is subjected to irradiation crosslinking to obtain hydrogel fabric.

7. The hydrogel fabric as described in claim 6, characterized in that, The inert solvent 4 is selected from the group consisting of ethanol, methanol, water, or combinations thereof; and / or The catalyst 4 is selected from the group consisting of sodium hydroxide, sodium bicarbonate, potassium hydroxide, lithium hydroxide, or combinations thereof.

8. The hydrogel fabric as described in claim 6, characterized in that, The amino-modified reaction precursor N is selected from the following group: Hyperbranched polypropyleneimide; Where m ranges from 3000 to 70000.

9. The hydrogel fabric as described in claim 6, characterized in that, The crosslinking agent C is selected from the following group: N,N'-methylenebisacrylamide (MBA), triethanolamine, titanate crosslinking agent (TA), epichlorohydrin, and glutaraldehyde.

10. Use of the cyanopolymer as claimed in claim 1 or the hydrogel fabric as claimed in claim 6, characterized in that, i) Used for the adsorption and separation of metal ions; ii) Used to prepare isotopes 99 Mo reactor.